Aerosol Impact on UV Solar Irradiance and Diffuse Fraction - Codrean Andrea; Bunoiu Madalin; Paulescu Marius (Annals of West University of Timisoara: Physics)
Aerosols modify the solar irradiance levels in the ultraviolet (UV) spectral band and, as a result, influence the magnitude of the biological effects of solar radiation. Also, aerosols contribute to the changes in nature (direct/diffuse) of the UV solar radiation received by a biological organism. This work quantitatively evaluates the aerosol effects on all components of solar UV irradiance (direct-normal, diffuse and global) under clear sky conditions. A note of originality is given by the wide perspective and the depth of detail in which the influence of aerosols in the UV band is captured. In addition to the common parameters, such as aerosol nature and the atmospheric aerosol loading, fine properties of aerosols, such as absorptivity and asymmetry factor, are considered. A distinctive feature of this study is given by the analysis of the effects of aerosols on the UV diffuse fraction. In general, changes in aerosol properties substantially change the direct-normal and diffuse components of UV solar irradiance and, to a lesser extent, the global component. The diffuse fraction in the UV band decreases notably with the increase of the Ångström turbidity coefficient and the Ångström exponent. Differently, the diffuse fraction is much less sensitive to the variation of the single scattering albedo and the asymmetry factor.